Ruler, Rival, Exile (Of Crowns and Glory-Book 7) - Morgan, Rice (Lukeman Literary, 2017)
"Morgan Rice has come up with what promises to be another brilliant series, immersing us in a fantasy of valor, honor, courage, magic and faith in your destiny. Morgan has managed again to produce a strong set of characters that make us cheer for them on every page....Recommended for the permanent library of all readers that love a well-written fantasy." --Books and Movie Reviews, Roberto Mattos (regarding Rise of the Dragons) RULER, RIVAL, EXILE is book #7 in Morgan Rice's bestselling epic fantasy series OF CROWNS AND GLORY, which begins with SLAVE, WARRIOR, QUEEN (Book #1), a free download. With Delos in ruins, Ceres, Thanos and the others set sail for the last corner of freedom in the Empire: the isle of Haylon. There, they hope to regroup with the few freedom fighters left, fortify the island, and make a spectacular defense against the hordes of Felldust. Ceres soon realizes that if they are to have any hope of defending the isle, she will need more than conventional skills: she will have to break the sorcerer's spell and regain the power of the Ancient Ones. And yet for this she must journey, alone, take the river of blood to the darkest cave in the realm, a place where neither life nor death exists, where she is more likely to come out dead than alive. The First Stone Irrien, meanwhile, is determined to keep Stephania as his slave and to oppress Delos. But the other Stones of Felldust may have other plans. RULER, RIVAL, EXILE tells an epic tale of tragic love, vengeance, betrayal, ambition, and destiny. Filled with unforgettable characters and heart-pounding action, it transports us into a world we will never forget, and makes us fall in love with fantasy all over again. "An action packed fantasy sure to please fans of Morgan Rice's previous novels, along with fans of works such as The Inheritance Cycle by Christopher Paolini.... Fans of Young Adult Fiction will devour this latest work by Rice and beg for more." --The Wanderer, A Literary Journal (regarding Rise of the Dragons) Book #8 in OF CROWNS AND GLORY will be released soon!
Keywords: Sci-fi, fantasy; Dobrodružství, napětí, fantasy